2022
DOI: 10.1523/jneurosci.1020-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Memory Processing during REM Sleep with Implications for Post-Traumatic Stress Disorder

Abstract: REM sleep is important for the processing of emotional memories, including fear memories. Rhythmic interactions, especially in the theta band, between the medial prefrontal cortex (mPFC) and limbic structures are thought to play an important role, but the ways in which memory processing occurs at a mechanistic and circuits level are largely unknown. To investigate how rhythmic interactions lead to fear extinction during REM sleep, we used a biophysically based model that included the infralimbic cortex (IL), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…We argue that the frightening nightmare experience might have activated structures belonging to the brain aversive system (BAS) to produce paradoxical kinesia. Indeed, emotional memories, including fear memories, are processed during REM sleep and involve interactions between the amygdala and the infralimbic medial prefrontal cortex in humans [ 9 ]. Patients undergoing stereotaxic neurosurgery reported strong feelings of fear, impending death or non-localized pain suffering caused by electrical stimulation of the inferior colliculus (IC), periaqueductal gray or amygdala [ 10 , 11 ], structures which in humans and non-humans belong to the BAS.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the frightening nightmare experience might have activated structures belonging to the brain aversive system (BAS) to produce paradoxical kinesia. Indeed, emotional memories, including fear memories, are processed during REM sleep and involve interactions between the amygdala and the infralimbic medial prefrontal cortex in humans [ 9 ]. Patients undergoing stereotaxic neurosurgery reported strong feelings of fear, impending death or non-localized pain suffering caused by electrical stimulation of the inferior colliculus (IC), periaqueductal gray or amygdala [ 10 , 11 ], structures which in humans and non-humans belong to the BAS.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of EEG data driven modeling, recent studies have shown the importance of periodic current sources to retrieve real spatiotemporal signals, see [6,7]. HH neural networks have also been used recently to model the effect of specific frequency stimulation to help patients suffering from Post-Traumatic Stress Disorder (PTSD), see [8].…”
Section: Introductionmentioning
confidence: 99%